A new genus of dipnoiformes from the Cretaceous of Brazil - Toledo, Carlos E.V.; Sousa, Eliane P. de; Medeiros, Manuel A.A.; Bertini, Reinaldo J. [UNESP] (Academia Brasileira de Ciências, 2011)
A Formação Alcântara, uma importante unidade estratigráfica do início do Cenomaniano no Brasil, foi depositada sob condições transicionais (estuarinas), e o seu registro fóssil inclui restos fragmentários de vegetais, peixes, crocodilomorfos, pterossauros e dinossauros, com uma notável diversidade de placas dentárias de dipnoiformes. O material de dipnoiformes aqui reportado compreende um novo taxon, Equinoxiodus alcantarensis gen. et sp. nov. A maioria dos morfótipos de vertebrados continentais coletados na Formação Alcântara são similares a faunas cronocorrelatas do norte da África, mas este novo gênero de Dipnoiformes indica algum grau de isolamento paleogeográfico e endemismo, provavelmente causado pelo alargamento do Oceano Atlântico equatorial no início do Cenomaniano, que pode ter afetado, de forma seletiva, algumas espécies.

The Alcântara Formation, an important stratigraphic unit from the early Cenomanian of Brazil, was deposited under transitional (estuarine) conditions, and its fossil record includes fragmentary remains of plants, fishes, crocodylomorphs, pterosaurs and dinosaurs, with a noteworthy diversity of dipnoiformes tooth plates. The dipnoiformes material reported here comprises a new taxon, Equinoxiodus alcantarensis, gen. et sp. nov. Most of the identified morphotypes of continental vertebrates collected in the Alcântara Formation are similar to chronocorrelative faunas from Northern Africa, but this new genus of Dipnoiformes indicates some degree of paleogeographic isolation and endemism. This was probably caused by the widening of the equatorial Atlantic Ocean during the early Cenomanian, which may have selectively affected some species.
Keywords: Dipnoiformes; neoceratodontídeos; Equinoxiodus alcantarensis gen. et sp. nov.; Cretáceo; Dipnoiformes; neoceratodontids; Equinoxiodus alcantarensis gen. et sp. nov.; Cretaceous